Systematic reviews as a tool for planning and interpreting trials - Bath, Philip M.W.; Gray, Laura J. (2009)
Background Systematic reviews followed by ameta-analysis are carried out in medical research to combine the results of two or more related studies. Stroke trials have struggled to show beneficial effects and meta-analysis should be used more widely throughout the research process to either speed up the development of useful interventions, or halt more quickly research with hazardous or ineffective interventions.